Design aspects of coherent optical networks - Fioretti, A.; Rocchini, C.A. (Workshop on the Future Trends of Distributed Computing Systems in the 1990s: Proceedings, 1988)
Aspects and functions of an integrated-service multichannel network are analyzed. The interaction between technological constraints and network architecture is discussed. A management scheme fully compatible with open systems interconnection is presented. This scheme shows the increased flexibility of a multichannel integrated network, which is derived from the possibility of reconfiguring the network and of automatically balancing the traffic between different channels.< >